Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 432902 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Passeriformes", { "or" : [ "Country is United States of America", "Country is Canada", "Country is Mexico" ] }, "HasCoordinate is true", "HasGeospatialIssue is false", "BasisOfRecord is Specimen", "Year is greater than or equal to 1950" ] } The dataset includes 432902 records from 108 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0059707-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences